WAIS Divide ice core suggests sustained changes in the atmospheric formation pathways of sulfate and nitrate since the 19th century in the extratropical Southern Hemisphere - E. D. Sofen (Atmospheric Chemistry and Physics, 2014)
The 17O excess (Δ17O = δ17O−0.52 × δ18O) of sulfate and nitrate reflects the relative importance of their different production pathways in the atmosphere. A new record of sulfate and nitrate Δ17O spanning the last 2400 years from the West Antarctic Ice Sheet Divide ice core project shows significant changes in both sulfate and nitrate Δ17O in the most recent 200 years, indicating changes in their formation pathways. The sulfate Δ17O record exhibits a 1.1 ‰ increase in the early 19th century from (2.4 ± 0.2) ‰ to (3.5 ± 0.2) ‰, which suggests that an additional 12–18% of sulfate formation occurs via aqueous-phase production by O3, relative to that in the gas phase. Nitrate Δ17O gradually decreases over the whole record, with a more rapid decrease between the mid-19th century and the present day of 5.6 ‰, indicating an increasing importance of RO2 in NOx cycling between the mid-19th century and the present day in the mid- to high-latitude Southern Hemisphere. The former has implications for the climate impacts of sulfate aerosol, while the latter has implications for the tropospheric O3 production rate in remote low-NOx environments. Using other ice core observations, we rule out drivers for these changes other than variability in extratropical oxidant (OH, O3, RO2, H2O2, and reactive halogens) concentrations. However, assuming OH, H2O2, and O3 are the main oxidants contributing to sulfate formation, Monte Carlo box model simulations require a large (≥ 260%) increase in the O3 / OH mole fraction ratio over the Southern Ocean in the early 19th century to match the sulfate Δ17O record. This unlikely scenario points to a~deficiency in our understanding of sulfur chemistry and suggests other oxidants may play an important role in sulfate formation in the mid- to high-latitude marine boundary layer. The observed decrease in nitrate Δ17O since the mid-19th century is most likely due to an increased importance of RO2 over O3 in NOx cycling and can be explained by a 60–90% decrease in the O3 / RO2 mole fraction ratio in the extratropical Southern Hemisphere NOx-source regions.